The Next Generation Leader 5 essentials for those who will shape the future - Stanley, Andy (Sisters, Ore. Multnomah, 2003)
Ready or not, you're next! It's time to shape the future, and those who will do so are in training today. Learn what it takes to lead with courage, then follow with character. Embrace the basics, and you'll master the challenges of generations to come.
Keywords: Christian leadership